2013
DOI: 10.1002/jssc.201200664
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐assisted extraction combined with on‐line solid phase extraction followed by ultra‐high‐performance liquid chromatography with tandem mass spectrometric determination of benzotriazole UV stabilizers in marine sediments and sewage sludges

Abstract: Benzotriazole ultra-violet stabilisers are compounds widely used in personal care products, which can reach the environment after passing through wastewater treatment plants. In this work, we develop a novel method to evaluate the presence of seven compounds in marine sediments and sewage sludges using microwave-assisted extraction followed by a clean-up step based in on-line solid phase extraction coupled to ultra-high-performance liquid chromatography with MS/MS detection. This method allows for fast and eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…Efficient extraction of some benzotriazole UV stabilizers has been a challenge as reported previously [45]. However, satisfactory recoveries were obtained for the benzotriazole UV stabilizers from fish filet and fish belly samples, comparable with those for Table 3 Recoveries (%, mean ± SD, n = 3) of the UV absorbents.…”
Section: Methods Validationsupporting
confidence: 70%
See 3 more Smart Citations
“…Efficient extraction of some benzotriazole UV stabilizers has been a challenge as reported previously [45]. However, satisfactory recoveries were obtained for the benzotriazole UV stabilizers from fish filet and fish belly samples, comparable with those for Table 3 Recoveries (%, mean ± SD, n = 3) of the UV absorbents.…”
Section: Methods Validationsupporting
confidence: 70%
“…Montesdeoca-Esponda et al [45] observed co-elution of some benzotriazole UV stabilizers (e.g., UV-326, UV-327 and UV-328) on an octadecyl silica-based RP UHPLC column. Although complete separation is not indispensable in SRM mode, sufficient separation helps to improve detectability and to reduce ion suppression [58], whereas co-elution may impair proper quantification of the analytes due to competitive ionization [34].…”
Section: Optimization Of Uhplc-ms/msmentioning
confidence: 98%
See 2 more Smart Citations
“…Both types of UV filter, benzophenone and benzotriazole derivatives, have been extracted from sediments and sludges using MW energy [26,46].…”
Section: Uv Filtersmentioning
confidence: 99%